PTH-044 Effect of renal failure on the outcome of upper gi haemorrhage including risk scoring. (June 2019) - Murray, Iain A; Haddock, Rosie; Menzies, Alisdair; Fuchtbauer, David; Laursen, Stig B; Michell, Nick; Stanley, Adrian J
Abstract : Introduction: Renal failure is associated with poorer outcome following upper gastrointestinal haemorrhage (UGIH) and is a parameter in some pre-endoscopy risk stratification scores which can be used to identify low-risk patients who may avoid admission. We studied the outcome of patients admitted with UGIH in relation to their renal function and risk stratification scores. Methods: Prospectively collected data from a 1-year international multi-centre study of consecutive patients presenting with UGIH. Demographics, endoscopic findings, treatment and outcomes were recorded. eGFR was determined retrospectively from admission creatinine. If eGFR was <60 ml/minute, it was recorded whether this was acute kidney injury (AKI) or chronic kidney disease (CKD) by review of electronic patient notes. Glasgow Blatchford (GBS), admission Rockall (aRS), AIMS65 and PNED scores were determined. Need for endoscopic therapy, transfusion, surgery, rebleeding >7days and 30-day mortality rates were recorded. Results: Mains findings are shown in table 1 as median or percentage except where indicated. Conclusions: Patients admitted with UGIH and renal impairment are older and more likely to be female, than those with normal renal function. Transfusion requirements, need for endoscopic therapy, rebleed rate and mortality (bleed and non-bleed related) and are all increased in this group. GBS identifies low risk patients with AKI or CKD with high sensitivity, although few low risk patients are in this group. No other commonly used pre-endoscopy risk score is accurate in identifying low-risk patients with renal impairment.